Influence of Intervarietal and Interspecific Crosses on Seed Set of Gladiolus under Mid- hill Environments of Dailekh Condition - Poon, Tul Bahadur; Pokhrel, Anil; Shrestha, Subash; Sharma, Shasi R; Sharma, Khem R; Dev, Maha BL (Nepal Journal of Science and Technology, 2013)
Twelve intervarietal crosses and ten interspecific crosses of gladiolus were tested separately in RCBD, each with 4 replications in the field of Agriculture Research Station, Dailekh from 2010 to 2011.The objective of the study was to find the potentiality of seed set in different crosses within and between the species. Under intervarietal crosses, high pooled capsule set per spike resulted in ‘Ginger Red x G-4’ (95.0 %), ‘G-4 x American Beauty’ (92.5%), ‘Intrepid x G-4’(92.5%), ‘G-4 x Intrepid’ (91.7%), ‘American Beauty x G-4’(88.5%) and ‘Intrepid x American Beauty’(83.15%),but ‘Ginger Red x American Beauty’ and ‘Ginger Red x Intrepid’ produced the lowest pooled capsule set per spike with 50.1% and 53.8% respectively. ‘Intrepid x G-4’ produced the highest pooled number of seed sets with 66.0 per capsule followed by ‘G-4 x American Beauty’ with 44.0 and ‘G-4 x Intrepid’ with 44.0 while both ‘Ginger Red x American Beauty’ and ‘Ginger Red x Intrepid’ produced the lowest pooled number of seeds with 2.0 per capsule. Under the interspecific crosses, Pooled number of seed set per capsule was inconsequentially high in ‘Psittacinus hybrid x G-4’ with 56.0, ‘Intrepid x Psittacinus hybrid’ with 54.0 and ‘White Prosperity x Psittacinus hybrid’ with 52.0. The seed set due to the effects of present crosses of gladiolus are more satisfactorily successful than those in the previous studies. Incorporation of genotype ‘G-4’ and ‘Intrepid’ both as female and male parents have contributed to high number of seeds per capsule presumably due to inherent varietal trait coupled with favorable environment for triggering seed set. Nepal Journal of Science and Technology Vol. 13, No. 1 (2012) 17-24 DOI: http://dx.doi.org/10.3126/njst.v13i1.7394